2016
DOI: 10.3390/rs8050375
|View full text |Cite
|
Sign up to set email alerts
|

An Object-Based Image Analysis Approach for Detecting Penguin Guano in very High Spatial Resolution Satellite Images

Abstract: Abstract:The logistical challenges of Antarctic field work and the increasing availability of very high resolution commercial imagery have driven an interest in more efficient search and classification of remotely sensed imagery. This exploratory study employed geographic object-based analysis (GEOBIA) methods to classify guano stains, indicative of chinstrap and Adélie penguin breeding areas, from very high spatial resolution (VHSR) satellite imagery and closely examined the transferability of knowledge-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 73 publications
2
39
0
Order By: Relevance
“…Chabot and Francis () reported that automated counts of waterbirds were within 3%–5% of human counts across 16 applications. Recent improvements of UAV‐based counting include utilizing hyperspectral data (Beijboom et al., ; Witharana & Lynch, ), pixel‐shape modelling (Liu et al., ) and combining background subtraction with machine learning (Torney et al., ) (Figure b). Recent efforts to count animals use deep learning neural networks are promising, but require tens of thousands of training images gathered by human annotation (Bowley et al., ).…”
Section: Countingmentioning
confidence: 99%
“…Chabot and Francis () reported that automated counts of waterbirds were within 3%–5% of human counts across 16 applications. Recent improvements of UAV‐based counting include utilizing hyperspectral data (Beijboom et al., ; Witharana & Lynch, ), pixel‐shape modelling (Liu et al., ) and combining background subtraction with machine learning (Torney et al., ) (Figure b). Recent efforts to count animals use deep learning neural networks are promising, but require tens of thousands of training images gathered by human annotation (Bowley et al., ).…”
Section: Countingmentioning
confidence: 99%
“…These oversegmented results were then fed into the chessboard segmentation algorithm to be fine-tuned and merged, resulting in more appropriate final segmentation results without directly optimizing the SP. In a similar study, Witharana and Lynch [31] combined the segmentation derived from the multi-threshold segmentation (MTS) algorithm with that derived from the MRS to improve segmentation results without applying an intensive trial-and-error process. In their method, MTS is first applied to the image to generate undersegmented, simplified image objects.…”
Section: Related Workmentioning
confidence: 99%
“…Studies on parametrizing SP can be categorized into two general groups: supervised approaches [21,30,31,40], and unsupervised approaches [17,20,22,29]. With supervised methods, the goal is to identify an optimal segmentation (or set of segmentations) by evaluating the overlap of ground-truth reference polygons and computer-generated image segments.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to compare the accuracies of the two classification results, three commonly used evaluation metrics were adopted: accuracy, precision, and recall [27,54,55] …”
Section: Accuracy Assessment and Comparisonmentioning
confidence: 99%